2020
DOI: 10.1101/2020.04.23.051870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mechanics of Temporal Interference Stimulation

Abstract: AbstractWe utilize single neuron models to understand mechanisms behind Temporal Interference (TI) stimulation (also called “Interferential Stimulation”). We say that a neuron exhibits TI stimulation if it does not fire for a high-frequency sinusoidal input, but fires when the input is a low-frequency modulation of the high-frequency sinusoid (specifically that generated by addition of two high frequency sinusoids with a small difference in their frequencies), while the maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…From the transition from LIF to EIF it is clear that adding a non-linearity is not sufficient to achieve stimulation with the TI-signal at lower intensities than with the single sinusoidal signal. This is in agreement with Cao and Grover (2020) [16]. Moreover, by increasing the effect of the nonlinearity (∆ T ↑), it becomes clear that the gap between the thresholds of the sine and TI-signal becomes bigger.…”
Section: A If Modelssupporting
confidence: 91%
See 2 more Smart Citations
“…From the transition from LIF to EIF it is clear that adding a non-linearity is not sufficient to achieve stimulation with the TI-signal at lower intensities than with the single sinusoidal signal. This is in agreement with Cao and Grover (2020) [16]. Moreover, by increasing the effect of the nonlinearity (∆ T ↑), it becomes clear that the gap between the thresholds of the sine and TI-signal becomes bigger.…”
Section: A If Modelssupporting
confidence: 91%
“…Changing the beat frequency did not seem to have an influence on the threshold [2], [11]. To model TI-stimulation, it was found that IF-neurons are not sufficient to reproduce the experimental behaviour on single neuron level [16]. However, when IF-neurons are placed in a network and GABA b postsynaptic inhibition is included, the computational results were in line with experimental observations of TI-stimulation [17].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…For instance, experimental findings suggest that the stimulation effects depend on time constants of axons' membrane and slow GABAergic inhibition (GABA b -type) 53 . indicating selective responsiveness depending on neuron types and properties 54 .…”
Section: Discussionmentioning
confidence: 99%
“…The concept of tTIS was initially proposed and validated on the hippocampus of rodents 40 and was then further tested through computational modelling [42][43][44][45][46] and in first applications on cortical areas in humans 47,48 . tTIS requires two pairs of electrodes to be placed on the head, each pair delivering a high frequency alternating current.…”
Section: Introductionmentioning
confidence: 99%